Answer: All of thé above
Step-by-step explanation:
Answer:
Step-by-step explanation:
38.
![M=\frac{1}{2} (x_{1}+x_{2})\\2M=x_{1}+x_{2}\\x_{1}=2M-x_{2}](https://tex.z-dn.net/?f=M%3D%5Cfrac%7B1%7D%7B2%7D%20%28x_%7B1%7D%2Bx_%7B2%7D%29%5C%5C2M%3Dx_%7B1%7D%2Bx_%7B2%7D%5C%5Cx_%7B1%7D%3D2M-x_%7B2%7D)
37.
![S=\frac{ab^2}{3} \\3S=ab^2\\b^2=\frac{3S}{a} \\b=\pm\sqrt{\frac{3S}{a} }](https://tex.z-dn.net/?f=S%3D%5Cfrac%7Bab%5E2%7D%7B3%7D%20%5C%5C3S%3Dab%5E2%5C%5Cb%5E2%3D%5Cfrac%7B3S%7D%7Ba%7D%20%5C%5Cb%3D%5Cpm%5Csqrt%7B%5Cfrac%7B3S%7D%7Ba%7D%20%7D)
D.630
Step-by-step explanation:
i did the math and got that
Let the two numbers be x and y
Then
x + y = 60
And
x - y = 2
x = y + 2
Putting the value of x in the first equation we get
x + y = 60
y + 2 + y= 60
2y + 2 = 60
2y = 60 - 2
2y = 58
y = 58/2
y = 29
Now putting the value of y in the first equation we get
x + y = 60
x + 29 = 60
x = 60 - 29
x = 31
So the value of the two numbers comes out to be 31 and 29. I hope the procedure is clear enough for you to understand.
Answer: D
Step-by-step explanation: